Women in Cankar’s novels and the unfinished novel Marta - Zupan Sosič, Alojzija (Slavia Centralis, 2023)
Today, the position of women both in European reality and in novels is similar to the position of real and fictional women at the beginning of the 20th century, so the discussion not only analysed the main female characters in Cankar’s novels, but also interpreted the construction of their identity, actualised through the prism of repatriarchalisation. Of Cankar’s ten novels, women are the main characters in as many as seven of them, and their image ranges from the conservative ambivalence of the saint-adulteress to the modern freedom seeker and restless traveller. Of all the characters in the novels, Francka is the most famous, a symbol of the suffering mother and the Slovenian nation as a whole. Her partial mythologising and idealisation preserves some stereotypical representations of women, which are obviously modernised in the novel Gospa Judit: Judit is Cankar’s most modern female character. Milena in the novel Milan and Milena is also characterised by innovative characteristics, which is an expression of the androgynous principle, a frequent solution to the re-evaluation of gender roles in “moderna” movement, while Marta is the strongest female character, also because of her androgyny: she is active, selfconfident and has common sense. If Cankar had finished the novel Marta, Slovenian literature would have been richer for another multifaceted female character. In his ten novels, Ivan Cankar not only criticised the conservative attitude towards women, but also criticised unjust capitalism as a whole, especially the perverse attitude towards children’s work and various sexual abuses.
Keywords: Cankar’s novels; (re)patriarchalisation; aesthetics of “moderna”; (non)stereotypical images of women; androgyny; saint-adulteress; Francka; Judit; Marta